Chitosan nanocomposites based on distinct inorganic fillers for biomedical applications - Duarte, Moura (2016)
AbstractChitosan (CHI), a biocompatible and biodegradable polysaccharide with the ability to provide a non-protein matrix for tissue growth, is considered to be an ideal material in the biomedical field. However, the lack of good mechanical properties limits its applications. In order to overcome this drawback, CHI has been combined with different polymers and fillers, leading to a variety of chitosan-based nanocomposites. The extensive research on CHI nanocomposites as well as their main biomedical applications are reviewed in this paper. An overview of the different fillers and assembly techniques available to produce CHI nanocomposites is presented. Finally, the properties of such nanocomposites are discussed with particular focus on bone regeneration, drug delivery, wound healing and biosensing applications.